ANALISIS PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN YANG TERDAFTAR DALAM INDEKS SRI-KEHATI - DWI A, SUKMARINGGA (Jurnal Akuntansi AKUNESA, 2015)
The purpose of this study was to determine the implementation of Corporate Social Responsibility indicators most widely disclosed by the company contained in the SRI-KEHATI index. The data used in this research is secondary data contained in annual reports or corporate sustainability report and for the kind of research is qualitative descriptive. The conclusion of this study is the current method of assessment GRI is the most widely used indicator by companies listed in the index SRI-KEHATI 2011-2014. Indonesian environment ministry has set PROPER as a basis for environmental responsibility. While ISO 26000 is more widely used as a direction in fulfilling their social responsibilities in accordance with corporate governance. In practice three indicators actually have some similarities that can be used simultaneously.Key words: Corporate Social Responsibility, GRI, ISO 26000, PROPER.